2014
DOI: 10.1093/cvr/cvu162
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-92a improves re-endothelialization and prevents neointima formation following vascular injury

Abstract: AimsMicroRNA (miR)-92a is an important regulator of endothelial proliferation and angiogenesis after ischaemia, but the effects of miR-92a on re-endothelialization and neointimal lesion formation after vascular injury remain elusive. We tested the effects of lowering miR-92a levels using specific locked nucleic acid (LNA)-based antimiRs as well as endothelial-specific knock out of miR-92a on re-endothelialization and neointimal formation after wire-induced injury of the femoral artery in mice.Methods and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 28 publications
7
89
0
5
Order By: Relevance
“…Furthermore, we found a reduced number of CD68 + monocytes/ macrophages accumulating in the lesions as well as a reduced number of proliferating Ki67 + SMCs within the vessel wall, and an impairment of neointima lesion development. As expected, the expression of the pro-angiogenic miR-92a target genes Sirt1 and Itga5 was strongly increased at 2 weeks after wire-induced injury [11] . Itga5 interacts with fibronectin, which represents the major component of the early extracellular matrix, and its expression has been shown to be an important prerequisite for vascular regeneration [12] .…”
Section: Research Highlightsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, we found a reduced number of CD68 + monocytes/ macrophages accumulating in the lesions as well as a reduced number of proliferating Ki67 + SMCs within the vessel wall, and an impairment of neointima lesion development. As expected, the expression of the pro-angiogenic miR-92a target genes Sirt1 and Itga5 was strongly increased at 2 weeks after wire-induced injury [11] . Itga5 interacts with fibronectin, which represents the major component of the early extracellular matrix, and its expression has been shown to be an important prerequisite for vascular regeneration [12] .…”
Section: Research Highlightsupporting
confidence: 82%
“…Neither ECs nor SMCs showed changed apoptotic rates following sole overexpression of miR-92a [11] . We then abrogated miR-92a expression following vascular injury by the use of two different strategies.…”
Section: Research Highlightmentioning
confidence: 88%
See 1 more Smart Citation
“…Among the miRNAs whose expression is regulated by developmental IGF-1 deficiency, upregulation of miR-125a-5p has been linked to impaired angiogenesis and endothelial dysfunction (Che et al 2014), endothelial apoptosis (Svensson et al 2014), and dysregulation of endothelial tight junctions (Reijerkerk et al 2013). miR-92a promotes atherosclerosis, endothelial dysfunction (Loyer et al 2014), and neointima formation (Daniel et al 2014). miR-126 is a biomarker of clinical atherosclerosis (Kim et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of miR-92a expression prevents endothelial activation and dysfunction in vivo and promotes the anti-inflammatory phenotype 113) . Another study showed that miR-92a inhibition improves re-endothelialization, which enhances functional recovery following vascular injury in vivo 114) . The described findings about miR-92a in atherosclerosis make it a potential therapeutic target in vascular pathology.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%